2016
DOI: 10.1111/sjop.12335
|View full text |Cite
|
Sign up to set email alerts
|

Assessing reading comprehension with narrative and expository texts: Dimensionality and relationship with fluency, vocabulary and memory

Abstract: Reading comprehension assessment should rely on valid instruments that enable adequate conclusions to be taken regarding students' reading comprehension performance. In this article, two studies were conducted to collect validity evidence for the vertically scaled forms of two Tests of Reading Comprehension for Portuguese elementary school students in the second to fourth grades, one with narrative texts (TRC-n) and another with expository ones (TRC-e). Two samples of 950 and 990 students participated in Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
2
8
0
5
Order By: Relevance
“…Finally, medium-to-large correlation coefficients were found between the TRC-n and TLC-n forms and the teachers' ratings regarding students' performance in oral reading fluency, listening, and reading comprehension, and high correlations were found with academic achievement indicators. Prior studies reported correlations of similar magnitude between these variables Shapiro, 2003, 2009;Gilmore and Vance, 2007;Viana et al, 2015;Santos et al, 2016a). These results suggest that the scores in the developed test forms are a fair representation of actual school achievement of the students.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Finally, medium-to-large correlation coefficients were found between the TRC-n and TLC-n forms and the teachers' ratings regarding students' performance in oral reading fluency, listening, and reading comprehension, and high correlations were found with academic achievement indicators. Prior studies reported correlations of similar magnitude between these variables Shapiro, 2003, 2009;Gilmore and Vance, 2007;Viana et al, 2015;Santos et al, 2016a). These results suggest that the scores in the developed test forms are a fair representation of actual school achievement of the students.…”
Section: Discussionsupporting
confidence: 64%
“…Finally, previous studies have also found medium-to-large correlation coefficients between teachers' ratings of students' reading skills and students' performance on standardized tests that assess reading and listening comprehension from kindergarten to the fifth grade Shapiro, 2003, 2009;Gilmore and Vance, 2007;Viana et al, 2015;Santos et al, 2016a).…”
Section: Introductionmentioning
confidence: 79%
“…The TRL allows a fast identification of at risk children who may need pedagogical adaptations and/or other intervention measures. This test enables an early intervention; in other words, this test enables not to jeopardize the future knowledge acquisition and school trajectory (Viana, 2009;Santos et al, 2017;Zuilkowski et al, 2019). Further research to gather evidence based on consequences of early testing may be useful to inform and motivate educators to adopt reading acquisition screening tools.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to identify and to intervene in reading acquisition difficulties as early as possible, for which diagnostic and intervention tools are necessary (Poulsen et al, 2017). Assessment is a fundamental step in the teaching process as it allows obtaining information that supports pedagogical decisions that will contribute to help students developing their skills (Viana, 2009;Santos et al, 2017;Zuilkowski et al, 2019). When referring to reading acquisition, early assessment is a necessary condition for early detection of difficulties with a consequent decision on intervention (Lyytinen, 2008;Hall and Burns, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Outras investigações comparam a compreensão leitora em textos narrativos e expositivos (e.g., BARETA et al, 2009;BAŞTUĞ, 2014;CADIME et al, 2017;CAPELLINI, 2015;ÇAKIR, 2008;MCNAMARA, OZURU;FLOYD, 2011;WOLFE, 2005). Baştuğ (2014), por exemplo, comparou, por meio do teste de Cloze, as habilidades de compreensão de leitura em alunos de 4º e 5º anos, observando que os participantes tinham um melhor desempenho no texto narrativo que no expositivo.…”
Section: Introductionunclassified